Las protesis oculares como alternativa para la reinserción social, por parte de los profesionales de la Salud Visual del cantón Babahoyo, octubre 2018 - abril 2019 - Lalaleo Yuccha, Deisy Pamela (2019)
The enormous importance of ocular prostheses within physical, psychological and anatomical health is a subject frequently overlooked and minimized within the canton of Babahoyo, however, ocular prostheses play a very important role for the psychological health of the patients. Patients in need of this device because this allows it to project and insert itself into society, since it gives it security, a better quality of life and undoubtedly improves their self-esteem. The main objective of this research was to analyze primary care in patients using ocular prostheses, which determined that the appropriate service was not being provided. Hence, in this research within the methodological part an exploratory and descriptive study was used, during its development retrospective and prospective data was used due to the present problematic in the investigation regarding the bibliographic and field compilation and we applied Surveys to the respective professionals, resulting in that of the 13 professionals surveyed for this research are understood that 69% are Optometrists, 23% Ophthalmologists and 8% Medical Technologist, it was also possible to determine that 69% of the professionals surveyed if they had patients in need of prostheses and only 31% did not have patients with this requirement, it could also be determined that of the 13 visual health professionals of the Babahoyo canton who carried out the survey, one hundred percent stated that if reintegration is helped to society because they are given greater security and improve their self este to. Conclusions - The lack of an awareness of visual health and the adaptation of ocular prostheses means that users do not perform constant exams to learn about their ocular prosthesis status.